The Peace of Nature and the Nature of Peace : Essays on Ecology, Nature, Nonviolence, and Peace. - Fiala, Andrew. (Value Inquiry Book Series, 2015)
The essays collected in The Peace of Nature and the Nature of Peace consider connections between ecology, environmental ethics, nonviolence, and philosophy of peace. Edited by Andrew Fiala, this book includes essays written by important scholars in the field of peace studies, pacifism, and nonviolence, including Michael Allen Fox, Andrew Fitz-Gibbon, Bill Gay, and others. Topics include: ecological consciousness and nonviolence, environmental activism and peace activism, the environmental impact of militarism, native and indigenous peoples and peace, food ethics and nonviolence, and other topics. The book should be of interest to scholars, students, and activists who are interested in the relationship between peace movements and environmentalism.